Answer :

We have,

4x3 - 12x2 + 11x - 5


Let, p (x) = 4x3 - 12x2 + 11x - 5


And, (2x – 1) = 0


2x = 1


x =


It is given that, (2x - 1) is a factor of p (x) so the remainder is equal to p()


p (2) = 4 ()3 - 12 ()2 + 11 () - 5


= 4 × - 12 × + 11 × - 5


= - 3 + - 5


= – 8


= 6 – 8


= - 2


Hence, option C is correct

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics